BATTLE OF AUTO-IMMUNITIES: GRAVES’ DISEASE AND RHEUMATOID ARTHRITIS: A BIDIRECTIONAL CAUSAL EFFECT - Lee, Yih Hoong; Ling, Amy Lee Mei; Yew, Ing Chiew; Ling, Guo Ruey; Lau, Eunice Yi Chwen (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Graves’ disease is an autoimmune disorder characterized by hyperthyroidism secondary to circulating thyroid autoantibodies. Co-existence with other autoimmune diseases such as vitiligo, chronic autoimmune gastritis and rheumatoid arthritis (RA) have been reported. We report a patient who developed RA more than 10 years following her diagnosis of Graves’ disease. CASE A 37-year-old female with Graves’ disease diagnosed at age 22 years presented with a 2 to 3-week history of multiple joint pains and morning stiffness involving both knees, ankles, elbows, and metacarpophalangeal joints (MCPJs). She did not have any preceding trauma, fever, genitourinary or gastrointestinal infections. There were no sicca symptoms, rashes, oral ulcers or constitutional symptoms. Examination revealed right knee and multiple MCPJ synovitis. She had a small diffuse goitre and no exophthalmos. Inflammatory markers were elevated with an ESR of 70 mm/H and CRP of 21.6 mg/L. She had mild hypochromic microcytic anaemia (Hb11.8 g/dL) and lymphopenia (1.3 103/uL). Rheumatoid factor and anti-Ro60 were both positive. Uric acid (277 umol/L) and FT4 (21.07 pmol/L) levels were normal. Knee joint aspirate culture and AFB were negative. Joint x-rays were unremarkable. Thyroid ultrasound showed enlarged thyroid lobes with coarse echotexture and increased vascularity. A rheumatology consult was obtained, and she was diagnosed with RA. She commenced on methotrexate and oral steroids which resulted in marked improvement in her joint condition. Her fT4 remained stable on low dose carbimazole. CONCLUSION Graves’ disease is associated with an increased risk of RA and vice versa. Hence, it is important to screen patients with inflammatory joint pain for RA to ensure prompt management and prevent long-term joint damage and other complications.